2017
DOI: 10.1186/s12983-017-0235-8
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs in the production of animal vocal sequences: insights from the structure of wild chimpanzee pant hoots

Abstract: BackgroundVocal sequences - utterances consisting of calls produced in close succession - are common phenomena in animal communication. While many studies have explored the adaptive benefits of producing such sequences, very little is known about how the costs and constraints involved in their production affect their form. Here, we investigated this issue in the chimpanzee (Pan troglodytes schweinfurthii) pant hoot, a long and structurally complex vocal sequence comprising four acoustically distinct phases – i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 61 publications
(74 reference statements)
3
53
1
Order By: Relevance
“…R. Soc. B 286: 20182900 studies of human language and recently shown also to apply to vocal sequences of geladas [4] and chimpanzees [18], suggests that comparable principles of self-organization [48] underpin these different combinatorial communication systems. This law has not previously been explored in gestural communication in humans or other species; our results provide new evidence of an important commonality between human language and primate gestural communication, with respect to the basic structural patterns underpinning how signals are combined into larger structures.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…R. Soc. B 286: 20182900 studies of human language and recently shown also to apply to vocal sequences of geladas [4] and chimpanzees [18], suggests that comparable principles of self-organization [48] underpin these different combinatorial communication systems. This law has not previously been explored in gestural communication in humans or other species; our results provide new evidence of an important commonality between human language and primate gestural communication, with respect to the basic structural patterns underpinning how signals are combined into larger structures.…”
Section: Discussionmentioning
confidence: 97%
“…This law has not previously been explored in gestural communication in humans or other species; our results provide new evidence of an important commonality between human language and primate gestural communication, with respect to the basic structural patterns underpinning how signals are combined into larger structures. In studies of this law in primate vocal communication [4,18], breathing-related constraints and energetic demands of vocal production were implicated as important drivers of the negative relationship between the number of calls in a sequence and their mean duration. Gestural sequences are not constrained by breathing patterns, as is the case for vocal sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninth, recent investigations of statistical regularities in primate vocal communication reveal patterns consistent with Zipf's law of abbreviation (i.e. frequently used words tend to become shorter) [Semple, Hsu & Agoramoorthy, ; Ferrer‐i‐Cancho et al ., ; but see Ferrer‐i‐Cancho & Hernández‐Fernández, for discussion about the law visibility] and with Menzerath's law (which predicts that longer sequences are made up of shorter constituents) (Gustison et al ., ; Fedurek, Zuberbühler & Semple, ; Gustison & Bergman, ) suggesting that common linguistic laws underlie the structure of vocal communication in human and non‐human primates.…”
Section: Theories Of the Origins Of Languagementioning
confidence: 99%
“…More recently, the size of vocal sequences uttered by wild gelada males (Theropithecus gelada) was found to be negatively correlated with the duration of the calls constituting the sequences, providing the first indication of Menzerath-Altmann Law conformity in a non-human primate [2]. Evidence of conformity to Menzerath-Altmann Law also comes from Chimpanzee pant hoots [11]. However, more taxa remain to be investigated, especially beyond primates, to develop a broader understanding of the occurrence and significance of such statistical patterns in animal vocalizations.…”
Section: Introductionmentioning
confidence: 99%